MARKETING COST ANALYSIS OF PROFIT OF PT. UNILEVER 2014-2018 - Rahman, Aulia; Rizky, Dini Amalia; Rosalia, Dinar; Azzahra, Dzikra (FEBI UIN Sunan Kalijaga, 2020)
Promotion is one of the variables in the marketing mix that is very important to be carried out by companies in marketing service products. Promotional activities not only function as a communication tool between the company and consumers, but also as a tool to influence consumers in purchasing or using services in accordance with their desires and needs. So this research was made to find out whether the promotional costs incurred affected unilever company profits in 2014-2018. This research is a type of quantitative research using secondary data with SPSS analysis tools. The results of the Multiple Linear Analysis test in this study prove the cost of promotion has a significant effect on the company's gross profit. However, it cannot be denied that there are other factors that can affect the company's gross profit apart from the promotionCosts